A Targeted Gain-of-Function Screen Identifies Genes Affecting Salivary Gland Morphogenesis/Tubulogenesis in Drosophila. - Maybeck, V.; Röper, K. (Genetics, 2009)
During development individual cells in tissues undergo complex cell-shape changes to drive the morphogenetic movements required to form tissues. Cell shape is determined by the cytoskeleton and cell-shape changes critically depend on a tight spatial and temporal control of cytoskeletal behavior. We have used the formation of the salivary glands in the Drosophila embryo, a process of tubulogenesis, as an assay for identifying factors that impinge on cell shape and the cytoskeleton. To this end we have performed a gain-of-function screen in the salivary glands, using a collection of fly lines carrying EP-element insertions that allow the overexpression of downstream-located genes using the UAS-Gal4 system. We used a salivary-gland-specific fork head-Gal4 line to restrict expression to the salivary glands, in combination with reporters of cell shape and the cytoskeleton. We identified a number of genes known to affect salivary gland formation, confirming the effectiveness of the screen. In addition, we found many genes not implicated previously in this process, some having known functions in other tissues. We report the initial characterization of a subset of genes, including chickadee, rhomboid1, egalitarian, bitesize, and capricious, through comparison of gain- and loss-of-function phenotypes.